2013
DOI: 10.1186/1471-2164-14-486
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses of the human retina identify unprecedented transcript diversity and 3.5 Mb of novel transcribed sequence via significant alternative splicing and novel genes

Abstract: Background: The retina is a complex tissue comprised of multiple cell types that is affected by a diverse set of diseases that are important causes of vision loss. Characterizing the transcripts, both annotated and novel, that are expressed in a given tissue has become vital for understanding the mechanisms underlying the pathology of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 87 publications
9
154
0
2
Order By: Relevance
“…The trichromatic visual system is one of the dramatic specializations present in the human lineage compared with other mammals. It is not entirely surprising that unique patterns of splicing and/or gene regulation may be related to these specializations (52,53). The model illustrates how incorporation of the e3-encoded sequence within the N-terminal region of CNGA3 may enhance the C-terminal PIP n regulation module by altering intersubunit interactions.…”
Section: Discussionmentioning
confidence: 97%
“…The trichromatic visual system is one of the dramatic specializations present in the human lineage compared with other mammals. It is not entirely surprising that unique patterns of splicing and/or gene regulation may be related to these specializations (52,53). The model illustrates how incorporation of the e3-encoded sequence within the N-terminal region of CNGA3 may enhance the C-terminal PIP n regulation module by altering intersubunit interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Examination of human RNA-seq data showed four additional variants occurred in genes with little or no expression in the retina making it unlikely they can cause retinal disease. 19 In addition, we also performed the same exclusions and prioritizations for all 14 compound heterozygous variants and found no promising candidates (Supplementary Table S2).…”
Section: Clinical Diagnosis Revealed a Typical Adult-onset Rp Phenotymentioning
confidence: 99%
“…We have reported that 100 million reads are necessary to fully cover both the human and mouse neural retina transcriptome (Grant et al 2011;Farkas et al 2012Farkas et al , 2013. Because transcriptome complexity varies between tissues and organisms, it is necessary to independently determine the appropriate depth of coverage for each RNASeq study (Wang et al 2008;Barbosa-Morais et al 2012;Gonzalez-Porta et al 2012).…”
Section: Next Generation Library Preparationmentioning
confidence: 99%